The impacts of unauthorised subdivisions of residential plots in Gadon Kaya, Kano City, Nigeria - Mahmoud Zubair Imam,; Katiman Rostam, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
﻿Illegal subdivisions of settlement plots (layouts) in developing countries are a common phenomenon. This practice normally resulted in lowering of the quality of life of the people living in such settlements. The aim of this paper is to identify and discuss the impact of such illegal subdivisions in a government approved Gadon Kaya settlement area in Kano city, Nigeria on the quality of life of its residents. A population sample of 110 residents was randomly picked and questionnaires administered to furnish the primary data. Other sources of data included field observations and interviews of selected stake holders. The analysis of the study shows that subdivision has indeed affected the quality of life in the area through reduced access, inadequate supply of water and electricity, poor sanitation, and inadequate ventilation. The findings imply that illegal subdivisions of settlement plots in Kano city would need to be discontinued and several recommendations are offered on possible measures to arrest further occurrence.